RELATIONSHIPS BETWEEN PRINCIPALS’ COMMUNICATION STYLES AND ADMINISTRATIVE EFFECTIVENESS IN PUBLIC SECONDARY SCHOOLS IN ANAMBRA STATE (UNIZIK Journal of Educational Management and Policy, 2026)
The need for administrative effectiveness in secondary school systems in Anambra State toensure quality and prompt delivery of educational services cannot be over-emphasized. Thisprompted the researchers to determine the relationship between principals’ communication stylesand administrative effectiveness in public secondary schools in Anambra State. Two researchquestions guided the study and two hypotheses were tested at. 05 level of significance.Correlation research design was adopted for the study. The population was 5,214 participantscomprising 264 principals and 4,950 teachers in public secondary schools in Anambra State.Proportionate stratified random sampling technique was used to draw the sample for study.Structured questionnaires were used for data collection. The instruments were face and constructvalidated. The researcher administered 285 copies of the instruments were administered to therespondents with the help of two research assistants using direct method and retrieval and 280copies were retrieved. Data were analyzed using Pearson Product Moment CorrelationCoefficient while the p-value was used to determine the significance of relationship at 0.05significant levels for all hypotheses. The results among others revealed that principals agreed thatthere is very high positive relationship between result-driven communication style andadministrative effectiveness in public secondary schools in Anambra. Accordingly, it wasrecommended among others that efforts should be made to encourage principals to adopt resultdriven communication style so as to improve on their administrative effectiveness.
Keywords: Communication Style, Administrative Effectiveness